2018
DOI: 10.29244/avl.2.1.15-16
|View full text |Cite
|
Sign up to set email alerts
|

Suspect feline infectious peritonitis pada kucing

Abstract: ABSTRAK:Feline infectious peritonitis (FIP) adalah penyakit menular akibat infeksi corona virus dan dapat berakibat kematian. Diagnosa FIP dijumpai pada seekor kucing dengan gejala anoreksia, lemas, perut membesar dan diare. Hasil pemeriksaan abdomen menunjukkan adanya undulasi positif diduga akibat penimbunan cairan di rongga abdomen. FIP tipe ini dijumpai adanya akumulasi cairan dalam rongga perut dan menyebabkan terjadinya pembesaran daerah abdomen dan disertai kesulitan bernafas. Berdasarkan pemeriksaan kl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…Figure 4b shows the embedded components of the device, which was positioned upright as a container for previously collected bull semen using an artificial vagina. Figure 4c shows a 16x2 LCD screen displaying the results of the bull semen quality analysis, including volume, viscosity, pH, and colour, in less than 5 s. Table 1 shows the semen of Friesian Holstein (FH) bulls analysed using an Arduino Mega 2560 based multisensor with a volume of 6 mL, medium viscosity, pH 6.5, and creamy white in colour, which is within the normal value of FH bull semen [8].…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Figure 4b shows the embedded components of the device, which was positioned upright as a container for previously collected bull semen using an artificial vagina. Figure 4c shows a 16x2 LCD screen displaying the results of the bull semen quality analysis, including volume, viscosity, pH, and colour, in less than 5 s. Table 1 shows the semen of Friesian Holstein (FH) bulls analysed using an Arduino Mega 2560 based multisensor with a volume of 6 mL, medium viscosity, pH 6.5, and creamy white in colour, which is within the normal value of FH bull semen [8].…”
Section: Resultsmentioning
confidence: 90%
“…Semen volume is conventionally measured by visual observation on a tube scale in millilitres of semen collected [12]. The normal volume of bull semen in a container is approximately 2-8 mL [8]. Based on normal bull volume data, the DIY water level sensor was designed using eight jumper cables arranged at a certain 3a).…”
Section: Discussionmentioning
confidence: 99%
“…Cara fruktosa dipecah dalam spermatozoa adalah salah satu dari beberapa factor yang dapat berdampak pada perubahan pH [19]. Plasma semen merupakan media netral yang mengangkut energi yang dibutuhkan oleh spermatozoa dan berfungsi sebagai buffer bagi sel spermatozoa, tingkat pH yang netral menunjukkan bahwa metabolisme spermatozoa yang lancer dan aktif berfungsi dengan baik, spermatozoa dapat mati lebih cepat jika pH berbeda yang dianggap normal [31]. Menurut hasil penelitian ini menunjukkan bahwa pH asam dapat meningkatkan konsentrasi spermatozoa dan menurunkan motilitas spermatozoa.…”
Section: B Ph Semenunclassified
“…In previous research, Kelor leaves supplementation in feed showed to be able to increase spermatozoa motility in Red Sokoto bucks [11]. Kelor leaves contained several bioactive compounds, phytosterols, and antioxidants [12] as well as Zn, which stimulates Leidig cells to produce testosterone [13], thus stimulates libido and affect sexual behavior.…”
Section: Introductionmentioning
confidence: 99%